$$\lim_{r\to 1} \frac{k-\frac{N(1-r^k)}{1-r^N}}{r-1}=-\frac{1}{2}k(k-N)$$

I've found this limit to be tricky. Everytime I take the derivative to apply l'Hopital's rule I get an indeterminant fraction again. But yet the symbolic solver says the limit exists.

  • $\begingroup$ There is a typo in your title, it should be $\frac12 k(N-k)$. $\endgroup$ – user Aug 6 at 16:47
  • $\begingroup$ need the following two identities to complete: $1-r^n = (1-r)\left(\sum \limits_{i=0}^{n-1}(r^i)\right)$ and $\sum \limits_{n=1}^{N-1} n = \frac{1}{2}N(N-1)$ $\endgroup$ – pico Aug 6 at 22:28
  • $\begingroup$ Yes these are both true, aren’t you familiar with that? $\endgroup$ – user Aug 6 at 22:38
  • $\begingroup$ Refer also to en.m.wikipedia.org/wiki/1_%2B_2_%2B_3_%2B_4_%2B_ $\endgroup$ – user Aug 6 at 22:47

We have

$$\frac{k - \frac{N(1-r^k)}{1-r^N}}{r-1}=\frac{ k(1-r)(1+r+\ldots+r^{N-1}) - N(1-r)(1+r+\ldots+r^{k-1) } }{(r-1)(1-r^N)}=$$


and by l'Hopital


$$\to \frac{k\frac{N(N-1)}{2}-N\frac{k(k-1)}{2}}{N}=\frac12\left(kN-k-k^2+k\right)=\frac12k(N-k)$$

| cite | improve this answer | |

Using standard notation for divided differences, we have

$$\begin{align} \frac{ f'(1) \left(g(r) - g(1)\right) - g'(1)\left(f(r) - f(1)\right)}{ (r - 1)\left(g(r) - g(1)\right)} &= \frac{ f'(1)g[r,1,1]-g'(1)f[r,1,1] }{ g[r,1]} \\ \lim_{r\to 1} \frac{ f'(1) \left(g(r) - g(1)\right) - g'(1)\left(f(r) - f(1)\right)}{ (r - 1)\left(g(r) - g(1)\right)} &= \frac{f'(1)g''(1)-g'(1)f''(1) }{2 g'(1)} \\ \lim_{r\to 1} \frac{ k \left(r^N-1\right) - N\left(r^k -1\right)}{ (r - 1)\left(r^N-1\right)} &= \frac{kN(N-1)-Nk(k-1)}{2N}\text{,} \end{align}$$

and therefore

$$ \lim_{r\to 1} \frac{ k \left(r^N-1\right) - N\left(r^k -1\right)}{ (r - 1)\left(r^N-1\right)} = \frac{k(N-k)}{2}\text{.} $$

| cite | improve this answer | |
  • $\begingroup$ @pico: the equalities are correct as I have written them. To understand where the $r-1$ in the denominator "went", think through what $f[r,1,1]$ and $g[r,1,1]$ in the first equality mean, and consider how the left side can be rearranged to make $f[r,1,1]$ and $g[r,1,1]$ appear. $\endgroup$ – K B Dave Aug 6 at 17:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.